The Anthroposcenic. Issue 3 (18th January 2017) - Matless, David
Abstract : This paper presents the 'Anthroposcenic' as a geographical contribution to debates around the Anthropocene, deploying the insights of cultural and historical geography to ask how thinking through landscape and time might shape understanding. The paper begins by elaborating on the term 'Anthroposcenic', foregrounding the ways in which landscape becomes emblematic of environmental transformation, and reflects further on geological wordplay in science and the humanities. The role of historical enquiry in addressing the times of the Anthropocene is considered, in terms of the dating of a proposed Anthropocene epoch, and the resonance of past geological debate. The possibilities of the Anthroposcenic are then demonstrated through studies of eroding coastal landscapes, drawing on contemporary and historical material from the English coast. Landscape here becomes emblematic of the Anthropocene, and shows how processes of environmental change are articulated through different geographical scales. Coastal studies also show past landscape achieving present resonance, and thereby how the Anthroposcenic may encompass historical material anticipatory of current debate. The paper reflects too on the ways in which questions of inheritance may frame Anthroposcenic enquiry. A specific Anthroposcene serves to open and close the paper.